A review of factors affecting the performance and impact of managed aquifer recharge projects: Insights from arid regions - Ali Al-Maktoumi (Journal of Groundwater Science and Engineering)
Managed Aquifer Recharge (MAR) is a strategic approach to artificially replenishing groundwater supplies and has become an integral component of global water resource management. The number of MAR projects has steadily increased in recent decades, yet many have failed to achieved their intended outcomes, underscoring the complexity of project implementation. This review is dedicated to examine existing research and reports on MAR performance and impacts, aiming to establish objective criteria for gauging the success and identify key factors influencing the effectiveness of MAR project. Five critical performance factors have been identified as major determinants of MAR performance: aquifer transmissivity, vertical permeability, availability of recharge water, recharge water quality, and aquifer thickness, geometry and boundary conditions. These factors are directly related to project success and significantly shape MAR outcomes. In addition, this review explores research-based strategies to improve MAR success, including cutting-edge methodologies, technological innovations, and integrated management approaches to address key challenges. The ultimate goal is to foster more efficient, effective, and sustainable MAR practices, thereby enhancing the resilience and sustainability of water resource management.